Комбіноване холодне видавлювання конічної порожнистої заготовки для виробу спеціального призначення - Сабол, Сергій Францович; Піманов, В. В.; Коробка, Є. М. (НТУ "ХПІ", 2015)
Запропоновано схему комбінованого видавлювання конічної порожнистої заготовки. За допомогою методу скінчених елементів (МСЕ) в програмному комплексі DEFORM-3D проведено теоретичний аналіз процесу. Визначено залежність зусилля процесу від переміщення пуансону, отримано розполіл нормальних напружень на матриці, пуансоні та виштовхувачі штампу. Приведено розподіл інтенсивності напружень та деформацій, а також ступеню використання ресурсу пластичності в здеформованій заготовці в моменті дії максимального зусилля процесу.

The scheme of the combined extrusion conical hollow shell. Using the finite element method (FEM) in the software complex theoretical analysis of the process. The dependence of the force of the punch from moving, obtained the distribution of normal stresses on the matrix, punch and ejector die. Distributions of intensity of the stresses and strains, as well as the degree of resource utilization in the plasticity of the deformed blank in the moment of action of maximum effort. There are proposed the scheme of the combined cold extrusion of conical hollow workpiece. Using the finite element method (FEM) in the software complex DEFORM-3D, the theoretical analysis of the process was conducted. There are identified dependence of the process’s forces of moving the punch, established the distribution of normal stresses on the matrix, punch and knock-out. Imposed the stress-strain state and the degree of using of the resource of plasticity of the deformed blank in the moment of action of maximum force.
Combined cold extrusion of conical hollow workpiece for special destination products
Keywords: метод скінчених елементів; зусилля; пуансон; напруження; матриця; деформація; пластичність; extrusion’s force; stress-strain state; plasticity